1994
DOI: 10.1016/0304-3959(94)90130-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned place preference paradigm: a novel approach for analgesic drug assessment against chronic pain

Abstract: In response to concerns over the clinical relevance of analgesic testing paradigms which involve acute nociceptive stimuli, the present research examined the utility of the conditioned place preference (CPP) paradigm as a novel approach for determination of analgesic drug efficacy against chronic nociception. Rats display preferences for environments that have been previously paired with positively reinforcing drugs; whether place preference to the negatively reinforcing effects of analgesic drugs in an animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(118 citation statements)
references
References 42 publications
5
110
3
Order By: Relevance
“…The lack of effect of MK-801 in place conditioning agrees with prior reports (Steinpreis et al 1995;Sufka 1994;Hoffman 1994;Tzschentke and Schmidt 1998, Sukhotina et al 1998Kim et al 1996;Kim and Jang 1997). However, some studies show that MK-801 may induce a CPP (Layer et al 1993a;Papp and Moryl 1994;Sufka 1994;Suzuki et al 1999;Panos et al 1999;Steinpreis et al 1995;Hoffman 1994;Biala and Kotlinska 1999;Papp et al 1996;Sukhotina et al 1998).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of effect of MK-801 in place conditioning agrees with prior reports (Steinpreis et al 1995;Sufka 1994;Hoffman 1994;Tzschentke and Schmidt 1998, Sukhotina et al 1998Kim et al 1996;Kim and Jang 1997). However, some studies show that MK-801 may induce a CPP (Layer et al 1993a;Papp and Moryl 1994;Sufka 1994;Suzuki et al 1999;Panos et al 1999;Steinpreis et al 1995;Hoffman 1994;Biala and Kotlinska 1999;Papp et al 1996;Sukhotina et al 1998).…”
Section: Discussionsupporting
confidence: 90%
“…However, some studies show that MK-801 may induce a CPP (Layer et al 1993a;Papp and Moryl 1994;Sufka 1994;Suzuki et al 1999;Panos et al 1999;Steinpreis et al 1995;Hoffman 1994;Biala and Kotlinska 1999;Papp et al 1996;Sukhotina et al 1998). Procedural and apparatus differences may account for these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, assessment of wellbeing and functional rehabilitation should also be included in tbe screening process of analgesic drugs at tbe preclinical level. Accordingly, improved but more complex approaches have recently been proposed to measure pain and its effects, like conditioned place preference/aversion paradigms (53,(82)(83)(84)(85)(86)(87)88), rat grimace scale (89), or spontaneous innate bebaviors {e.g., burrowing; refs. 90,91).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of AMI on rehabilitation do not seem to be related to hyperlocomotion (92,93). Furthertnore, prexdous sttidies assessing the effects of atialgesics on nonevoked pain behaviors, such as conditioned place preference/aversion tests (82,86,94), foot posture, and weight load (95), revealed that opioid agonists were not effective in reversing pain-related bebaviors. These results may, in part, explain why these analgesics do not provide adeqtiate pain relief of continuous spontaneous (nonevoked) pain in patients with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, researchers have used operant conditioning such as conditioned place avoidance, where a rodent will avoid a chamber or environment that it has previously paired with the experience of pain, or conditioned place preference, where a rodent will seek out a chamber or environment that it has paired with the relief of pain (reviewed in Navratilova et al, 2013). Although using this paradigm to study affective pain is, for the most part, relatively new, some studies have investigated inflammatory pain and found an enhanced conditioned place preference for morphine and low-dose NMDA receptor antagonist MK-801 in rats injected with CFA in their hind paws (Sufka, 1994). A similar study, however, observed that morphine-, cocaine-, and methamphetamine-induced place preference place preference was attenuated in the presence of inflammatory nociception by administration of formalin and carrageenan to the hind paw (Suzuki et al, 1996).…”
Section: Brain Inflammation Is Associated With Pain and Depressionmentioning
confidence: 99%